EXPLORING LOYALTY DRIVERS IN GEN-Z DIGITAL BANKING USERS: INSIGHTS FROM INDONESIA’S BLU BY BCA DIGITAL - Anak Agung Ayu Ngurah Agung Dewi Uttari Putri S. G.; Janice Carysa Siahaya (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to examine the influence of Quality of Service, Perceived Risk, Brand Leadership, and Price Perception on Customer Loyalty through Customer Satisfaction of GEN-Z Blu by BCA Digital Customers in Denpasar City. A quantitative approach was used with an online questionnaire survey to 95 active Blu by BCA Digital customer respondents who are in the Z generation. Data analysis applied PLS-SEM to test the relationship between variables. The results showed that all independent variables had a significant effect on customer satisfaction, which in turn influenced customer loyalty. These findings underscore the importance of ease of consumption, perceived value, reliability, perceived risk and service quality in building sustainable satisfaction. The study provides practical contributions to marketing and management strategies in the digital banking sector, as a basis for policies to improve customer experience and strengthen brand position in the competitive market.